Theoretical process of entrepreneurial family: developing the conceptual framework by using strategic entrepreneurship approach for the describing business sustainability - Ahmad Firdause, Md Fadzil; Mahwish, Jamil; Amber, Waqar (2020)
This conceptual paper reviews the related literature for describing an entrepreneurial family phenomenon. The study of sustainability in the family business becomes relatively attractive because it contributes to the development of the country towards GDP, innovation, and job creations. By using a strategic entrepreneurship approach, this study trying to develop the conceptual framework for describing of sustainability of family business phenomenon. The strategic entrepreneurship approach is undeveloped to explain of business sustainability phenomenon instead of other related approaches such as economics and management theories. Therefore, the purpose of this paper is to critically review how the elements of strategic entrepreneurship towards business sustainability which is overlooked by the previous scholars. The entrepreneurs who are an implement of strategic entrepreneurship have a significant focus not only on sustaining the competitive advantage but also on the growth and success of the ventures. In this century, financial and global crises highlight some questions towards a sustainable business model. In response to these issues, more research is required for developing a sustainable model for business. Despite a lot of work in the family business, the strategic entrepreneurship model with the sustainability of the family business is unexplored. The strategic entrepreneurship is immature to describe business sustainability in previous studies.